The association between high-sensitivity C-reactive protein and blood pressure in Yi people - Pan, Li; Li, Guoju; Wan, Shaoping; Yihuo, WuLi; Yang, Fang; Li, Zheng; Shan, Guangliang (BMC public health, 2019)
High-sensitivity C-reactive protein (hs-CRP) is a common risk factor for developing cardiovascular disease. However, there has been no study reporting the relationship between hs-CRP and blood pressure in Yi adults. The aim of this study is to investigate the association between hs-CRP and blood pressure in Yi adults. In this cross-sectional study, included subjects were 2916 Yi migrants or farmers aged 20-80 years, recruited by using a stratified cluster sampling method from Liangshan Yi Autonomous Prefecture of Sichuan Province in 2014. The directed acyclic graphs(DAG) was used to select a minimal sufficient adjustment sets of variables which would identification the unconfounded effect of hs-CRP and hypertension. Multiple linear and multinomial logit analysis were used to estimate the effect of hs-CRP on SBP/DBP/MAP/PP and the prevalence of prehypertension/hypertension after adjustment for the relevant confounders. The median level of hs-CRP was 1.20 (0.50-3.06)mg/L in Yi migrants, and 0.84(0.36-2.52) mg/L in Yi farmers, and the prevalence of high hs-CRP was 23.25%. For hs-CRP > 3 mg/L group, the adjusted PP tended to have lower values (β = - 1.49, 95%CI: - 2.49--0.49, P = 0.0034) compared with < 1 mg/L group. After adjusting for confounders, there were no significant association between hs-CRP and prehypertension/hypertension (P > 0.05). Our results suggest that high hs-CRP is prevalent in Yi people, and this study does not support hs-CRP as a risk factor of prehypertension or hypertension.